AN OPTIMIZATION SCHEME USING LINEAR PROGRAMMING IN A PRODUCTION LINE OF RITE FOODS LIMITED OSOSA - Erinle-Ibrahim, L. M.; Adewole, A. I.; Loyinmi, a. C.; Sodeinde, O. K. (FUDMA JOURNAL OF SCIENCES, 2020)
The research on the analysis of resource allocation for the maximization of profits using simplex The research of linear optimization in the production line of Rite food limited, Ososa, Odogbolu Local Government Area, Ogun State, Nigeria. In the study, it is observed that the company’s profits would be maximized if it produced more of Bigi Cola and Bigi Tropical soft drinks among those used for the analysis